Impact of Pan-Immune Inflammation Value on Short-Term Outcomes and Long-Term Prognosis in Patients with Type A Aortic Dissection - Cai H; Shourav; Shao Y; Shuangling S; Duan C; Zhang C; Wu QC (Journal of Inflammation Research)
Hao Cai,1,* FM Shourav,1,* Yue Shao,1 Sun Shuangling,2 Changzhu Duan,3 Cheng Zhang,1 Qing-chen Wu1 1Department of Cardiothoracic Surgery, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Biochemistry, Chongqing Medical and Pharmaceutical College, Chongqing, People’s Republic of China; 3Department of Cell Biology and Genetics, Chongqing Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qing-chen Wu, Department of Cardiothoracic Surgery, The First Affiliated Hospital of Chongqing Medical University, No. 1, Medical College Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Email wuqingchencqmu@126.com Cheng Zhang, Department of Cardiothoracic Surgery, The First Affiliated Hospital of Chongqing Medical University, No. 1, Medical College Road, Yuzhong District, Chongqing, 400016, People’s Republic of China, Email zhangchengcqmu@126.comBackground: Inflammatory responses are closely linked to the onset and progression of aortic dissection. The Pan-Immune Inflammation Value (PIV), a composite index derived from peripheral blood cell counts, has demonstrated prognostic relevance in multiple clinical conditions. However, its predictive value in acute Type A Aortic Dissection (TAAD) has not been well established. This study aims to investigate the relationship between preoperative PIV and both short-term and long-term outcomes in patients with acute TAAD.Methods: This retrospective study included acute TAAD patients who underwent surgical repair between September 2017 and December 2020. The optimal cutoff value for PIV was determined using receiver operating characteristic (ROC) curve analysis. Patients were then divided into low and high PIV groups based on this threshold. Short-term outcomes, including prolonged ICU stay (> 7 days) and postoperative complications were compared between groups using univariate and multivariate logistic regression analyses. Cox regression analyses were performed to identify independent predictors of long-term survival.Results: A total of 171 acute TAAD patients were included and stratified into low (n = 75) and high (n = 96) PIV groups based on preoperative values. In the high PIV group, patients had significantly longer surgery time, increased blood loss, greater volumes of red blood cell and plasma transfusions, longer ICU stays, and higher incidence of both overall and major complications (p=0.007, p=0.010, p=0.001, p=0.040, p=0.048, p< 0.001, p=0.003, respectively). Multivariate logistic regression analysis identified high preoperative PIV as an independent risk factor for prolonged ICU stay (> 7 days) (OR = 0.686, 95% CI, 0.303– 0.954, p = 0.027), overall complications (OR = 0.037, 95% CI, 0.005– 0.210, p = 0.002), and major complications (OR = 0.085, 95% CI, 0.026– 0.173, p = 0.017). Additionally, lower preoperative PIV levels were significantly associated with improved long-term survival (HR = 0.757, 95% CI, 0.378– 0.859, p = 0.020).Conclusion: PIV was identified as an independent predictor of prolonged ICU stay, overall and major postoperative complications, and long-term survival in patients with acute TAAD. As an integrative biomarker reflecting systemic immune-inflammatory status, PIV may serve as a valuable tool for early risk stratification and prognostic management.Keywords: type A aortic dissection, inflammatory response, overall survival, pan-immune inflammation value, prolonged ICU stay, postoperative complications